Modelling Municipal Cost Inefficiencies in the Frances Baard District of South Africa and Their Impact on Service Delivery - Brian Tavonga Mazorodze (Administrative Sciences)
Section 195(b) of South Africa’s Constitution calls for the efficient use of resources in public administration, while the White Paper on Local Government similarly emphasizes the efficient provision of basic services such as refuse collection and water. Despite these policy commitments, South African municipalities continue to be characterized by financial mismanagement and poor service delivery. In light of the limited empirical evidence on this issue, this study pursues two objectives. First, it estimates the levels of cost inefficiency in four local municipalities within the Frances Baard District from 2006 to 2023. Second, it determines how cost inefficiencies affect service delivery, focusing on water and refuse collection. Using a stochastic frontier analysis, several key results are confirmed. First, on average, the four municipalities are found to have spent 17.23% above the minimum cost required to deliver existing services. Second, service delivery is found to have been 23% lower than its potential. Third, operating costs and contracted services are found to have been key drivers of wasteful expenditure. Lastly, cost inefficiencies are found to have culminated in poor service delivery. Against this background, municipalities are urged to consider cutting non-essential operational spending such as entertainment and travel allowances, coupled with improved accountability on contracted services.